2022
DOI: 10.1016/j.tranon.2021.101322
|View full text |Cite
|
Sign up to set email alerts
|

NHS-IL12 and bintrafusp alfa combination therapy enhances antitumor activity in preclinical cancer models

Abstract: Highlights Combination therapy induced both adaptive and innate antitumor immunity. Combination therapy significantly enhanced antitumor activity. Combination therapy generated tumor antigen specific immune memory. Bintrafusp alfa mediated the reduction of lung metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Increases in T and NK cells were observed peripherally as well. This combination was also shown to decrease metastatic disease in 4T1 tumors ( 46 ). Overall, the combination of NHS-IL12 with other therapeutics such as ICIs and vaccine therapies, induces synergistic antitumor effects including immune stimulation and infiltration into tumors.…”
Section: Preclinical Studies Involving Nhs-il12mentioning
confidence: 97%
See 2 more Smart Citations
“…Increases in T and NK cells were observed peripherally as well. This combination was also shown to decrease metastatic disease in 4T1 tumors ( 46 ). Overall, the combination of NHS-IL12 with other therapeutics such as ICIs and vaccine therapies, induces synergistic antitumor effects including immune stimulation and infiltration into tumors.…”
Section: Preclinical Studies Involving Nhs-il12mentioning
confidence: 97%
“…This combination elicited synergistic antitumor efficacy associated with increased immune infiltration and expansion of Th1 cytokines, tumor-specific immune memory, CD8 + T and NK cell proliferation, and enhancement of tumor antigen-specific CD8 + T cells ( 43 , 44 ). Subsequent studies examined the combination of NHS-IL12 with bintrafusp alfa in multiple preclinical tumor models ( 45 , 46 ). Bintrafusp alfa is a first-in-class bifunctional fusion protein of monoclonal human IgG1 antibody blocking PD-L1 fused to TGFβRII extracellular domains, thereby sequestering the immunosuppressive cytokine, TGFβ ( 45 , 47 ).…”
Section: Preclinical Studies Involving Nhs-il12mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the role TGF-β plays in both tumor propagation and metastasis, there has been interest in combining TGF-β blockade with additional immunotherapeutic approaches. This includes a significant interest in concurrent CTLA-4 or PD-1/PD-L1 blockade [31][32][33], as well as combinations with immunocytokines [34], cytokine/chemokine blockade [35,36], oncolytic viruses [37], autologous tumor vaccination [38], and adoptive cell therapy [39]. The majority of these are outside the scope of this focused review.…”
Section: Importance Of the Transforming Growth Factor β (Tgf-β) Pathwaymentioning
confidence: 99%
“…Several preclinical studies have explored the combination of TGFβ and PD-1/PD-L1 inhibition as cancer therapy with uniformly positive results. However, as this approach has begun to emerge in clinical trials, progress has been difficult, with most trials failing to recapitulate the successes observed in animal models 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ( Table 1 ). Here, we summarize key clinical trials exploring concomitant TGFβ and PD-1/PD-L1 signal inhibition in solid tumors.…”
Section: Introductionmentioning
confidence: 99%